2021
DOI: 10.3389/fpsyt.2021.722874
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Creative Movement Therapies on Social Communication, Behavioral-Affective, Sensorimotor, Cognitive, and Functional Participation Skills of Individuals With Autism Spectrum Disorder: A Systematic Review

Abstract: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder affecting multiple developmental domains including social communication, behavioral-affective, sensorimotor, and cognitive systems. There is growing evidence for the use of holistic, whole-body, Creative Movement Therapies (CMT) such as music, dance, yoga, theater, and martial arts in addressing the multisystem impairments in ASD. We conducted a comprehensive quantitative and qualitative review of the evidence to date on the effects of CMT on mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 165 publications
0
11
0
Order By: Relevance
“…Research conducted in the first author's lab has evaluated effects of various creative movement (music and movement, and yoga) and physical activity interventions that were truly multisystem in nature due to key ingredients such as gross‐motor coordination/balance training, interpersonal synchrony/turn‐taking, as well as social interactions including, listening, singing/conversations, and leading/following (Kaur & Bhat, 2019; Kaur, Eigsti, & Bhat, 2021; Srinivasan, Eigsti, Gifford, & Bhat, 2016; Srinivasan, Eigsti, Neelly, & Bhat, 2016; Srinivasan, Kaur, et al, 2015; Srinivasan, Park, et al, 2015). Our recent systematic review found strong evidence for the positive effects of music and movement on the social communication, cognitive‐behavioral, and perceptuo‐motor skills of children with ASD (Amonkar et al, 2021). Such interventions may also facilitate changes in functional activation and connectivity to normalize brain functioning in ASD using recently identified neurobiomarkers (Su et al, 2020a, 2020b, 2021; Sharda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted in the first author's lab has evaluated effects of various creative movement (music and movement, and yoga) and physical activity interventions that were truly multisystem in nature due to key ingredients such as gross‐motor coordination/balance training, interpersonal synchrony/turn‐taking, as well as social interactions including, listening, singing/conversations, and leading/following (Kaur & Bhat, 2019; Kaur, Eigsti, & Bhat, 2021; Srinivasan, Eigsti, Gifford, & Bhat, 2016; Srinivasan, Eigsti, Neelly, & Bhat, 2016; Srinivasan, Kaur, et al, 2015; Srinivasan, Park, et al, 2015). Our recent systematic review found strong evidence for the positive effects of music and movement on the social communication, cognitive‐behavioral, and perceptuo‐motor skills of children with ASD (Amonkar et al, 2021). Such interventions may also facilitate changes in functional activation and connectivity to normalize brain functioning in ASD using recently identified neurobiomarkers (Su et al, 2020a, 2020b, 2021; Sharda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A significant instance of pervasive development being witnessed throughout the globe is the complex neurodevelopment condition called autism spectrum disorder (ASD) which impacts behavior, communication, and social interaction (1)(2)(3)(4). The scientific community has conducted several research studies in recent years to assess the incidence and prevalence of ASD (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…There is early evidence for the use of creative and general movement interventions based on engaging physical activity ideas using elements of gross‐motor coordination/balance training, whole‐body coordination games, interpersonal synchrony/turn‐taking, as well as social interactions including, listening, singing/conversations, and leading/following that can lead to multisystem, positive effects (Bhat et al, 2021; Cleffi et al, 2022; Kaur et al, 2021; Kaur & Bhat, 2019; Ketcheson et al, 2017; Srinivasan et al, 2021; Srinivasan & Bhat, 2013; Srinivasan, Eigsti, Gifford, & Bhat, 2016; Srinivasan, Eigsti, Neelly, & Bhat, 2016; Srinivasan, Kaur, et al, 2015; Srinivasan, Park, et al, 2015). A recent systematic review found medium to large positive effects of creative movement (music and movement, yoga, and martial arts) on the social communication, cognitive‐behavioral, and perceptuo‐motor skills of children with ASD (Amonkar et al, 2021).…”
Section: Discussionmentioning
confidence: 99%